RECENT SCENARIO OF CURRENT ACCOUNT DEFICIT IN INDIA - N, Yogambal (International Journal of Research -GRANTHAALAYAH, 2016)
Current Account Deficit topic deals with the meaning, the overview of the concept related with current scenario of the balance of trade. Through this paper we can come to know Gross Domestic position till recent date and impact of current account deficit. Just it gives idea whether current account deficit really harmful or good sign. This paper reveals the evaluation of current account deficit and also, reflection in various ways and also the implications of the reversals. It was concluded with few ideas which were shared as the suggestions to overcome the current account deficit.Global trends were analysed to know our country status.